Polifarmácia e adesão ao tratamento medicamentoso em pacientes com diabetes tipo 2 atendidos na rede pública de saúde no município de Fortaleza, Ceará - Penaforte, Kiarelle Lourenço (2012)
The Diabetes Mellitus type 2 (DM2) is an worldwide endocrine disorder. The therapy drug-based aims maintain metabolic control and improving the quality of life (QoL) of patients. The evolution of diabetes depends upon the management of the treatment by the patient, requiring the use of polypharmacy to maintain the levels of the glucose. We evaluated the occurrence of adherence or non-adherence to the drug therapy and the correlation with polypharmacy among patients with DM2 treated in the public system healthcare in Fortaleza, Ceará. The study was designed as exploratory cross-sectional comprising 235 patients with DM2, selected during the interview in the Health Centre Outpatient Anastácio Magalhães and University Hospital Walter Cantidio. The data were collected by self-report method. The criteria to adherence was considered follow at least 90% of the proposed treatment. Polypharmacy was defined as the use of two or more drugs and classified as; high (>5), moderate (4 to 5) and low (2 to 3) drugs. The statistical analysis was performed using Stata 5.0 and Graph pad prism 5.0, tests used were the Student t test, chi-square, ANOVA, with significance level of 95% (p <0.05). The study group consisted of 68.9% women, mean age of 59.3 years (± 12.7), mostly married (51.9%), with a predominance of few years of education and low income (48.4 % with 5-9 years of education and 49.5% with an average family of 1 minimum wage. We assessed the comorbidities and the results was the retinopathy (36.5%) as the most frequent complication followed by hypertension (30%). Furthermore most patients (50.2%) had between 1 and 10 years of disease and reported to have family support in the conduct of treatment (62%). Regarding the polypharmacy therapy was observed in 88.4% of cases, with a prevalence of moderate type. Were used on average 7.5 pills/person among 19 types of prescribed drugs. Adherence to prescribed therapy was reported by 88.2% of patients, with no association to polypharmacy. These results indicate that polypharmacy is a highly prevalent condition and is not invariably associated with poor adherence to therapy. Although the combination of drugs in a rational way often can maximize the efficiency of treatment, has to consider the clinical-epidemiologic profiles as greatest potential benefit.